2022
DOI: 10.3390/metabo12020157
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Natural Sources of Flavour and Aroma Metabolites from Solid-State Fermentation of Agro-Industrial By-Products

Abstract: Increasing consumer demand for natural flavours and fragrances has driven up prices and increased pressure on natural resources. A shift in consumer preference towards more sustainable and economical sources of these natural additives and away from synthetic production has encouraged research into alternative supplies of these valuable compounds. Solid-state fermentation processes support the natural production of secondary metabolites, which represents most flavour and aroma compounds, while agro-industrial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although not reported for volatile compounds in natural products, CAR/PDMS coating appears to be the most suitable for low MW analytes [13][14][15][16]. Lindsay et al [17] screened volatile profiles from food-grade agro-industrial by-products, such as apple, orange, carrot pomace, onion pulp, and kiwifruit peels. All extractions were carried out using HS-SPME with a 1 cm 50/30 µm DVB/CAR/PDMS (Supelco) fibre coupled with GC-MS.…”
Section: Solid-phase Microextractionmentioning
confidence: 99%
“…Although not reported for volatile compounds in natural products, CAR/PDMS coating appears to be the most suitable for low MW analytes [13][14][15][16]. Lindsay et al [17] screened volatile profiles from food-grade agro-industrial by-products, such as apple, orange, carrot pomace, onion pulp, and kiwifruit peels. All extractions were carried out using HS-SPME with a 1 cm 50/30 µm DVB/CAR/PDMS (Supelco) fibre coupled with GC-MS.…”
Section: Solid-phase Microextractionmentioning
confidence: 99%
“…Fermentation is a biochemical process alternative to produce a natural source of flavor and aroma metabolites, making the final product more attractive for consumption, with market acceptability. Lindsay et al [87] verified that secondary metabolites from the fermentation of by-products had high potential for adding value. The study was carried out using filamentous fungi and diverse byproducts, such as apple pomace, onion pulp, orange pomace, kiwifruit peels, carrot pomace, and olive pomace.…”
Section: Fermentation As a Byproduct Valorization Approachmentioning
confidence: 99%
“…Many of the volatile compounds found in GP have pleasant aromatic notes related to herbal, fruity, or floral perception [ 25 ]. Recently, Lindsay and co-workers [ 29 ] reported that some filamentous fungi find grape marc could be valuable sources of aromas. Aspergillus niger and Aspergillus oryzae are able to produce metabolites also associated with pleasant flavors, such as herbal notes, citrus (3-octanol), lavender, nectarine (3-octanone), cinnamon (E-cinnemaldehyde), or tropical fruits (ethyl tiglate) [ 29 ].…”
Section: Food Industry Applicationsmentioning
confidence: 99%
“…Recently, Lindsay and co-workers [ 29 ] reported that some filamentous fungi find grape marc could be valuable sources of aromas. Aspergillus niger and Aspergillus oryzae are able to produce metabolites also associated with pleasant flavors, such as herbal notes, citrus (3-octanol), lavender, nectarine (3-octanone), cinnamon (E-cinnemaldehyde), or tropical fruits (ethyl tiglate) [ 29 ]. The popularity of fruit teas is increasing in the world because of their antioxidant properties and their attractive taste.…”
Section: Food Industry Applicationsmentioning
confidence: 99%